Notes on Timarchos’ Iconography: Dioscuri Type - SMIRNOV, Svyatoslav (Historia i Świat, 2017)
The paper deals with the iconography of Timarchos’ ‘Dioscuri coinage’. The remarkable feature of these coins is that this coin type is nearly to be identical to that one of Greco-Bactrian king Eukratides I. The analysis of the stylistics shows the peculiar way of Timarchos’ iconography. Additionally, the ‘Dioscuri motif’ could have stressed the partnership between two rulers.